Paracrine recruitment and activation of fibroblasts by c‐Myc expressing breast epithelial cells through the IGFs/IGF‐1R axis. Issue 10 (23rd August 2019) - De Vincenzo, Anna; Belli, Stefania; Franco, Paola; Telesca, Marialucia; Iaccarino, Ingram; Botti, Gerardo; Carriero, Maria V.; Ranson, Marie; Stoppelli, Maria Patrizia
Abstract : Fibroblasts are among the most abundant stromal cells in the tumor microenvironment (TME), progressively differentiating into activated, motile, myofibroblast‐like, protumorigenic cells referred to as Cancer‐Associated Fibroblasts (CAFs). To investigate the mechanisms by which epithelial cells direct this transition, the early stages of tumorigenesis were exemplified by indirect cocultures of WI‐38 or human primary breast cancer fibroblasts with human mammary epithelial cells expressing an inducible c‐Myc oncogene (MCF10A‐MycER). After c‐Myc activation, the conditioned medium (CM) of MCF10A‐MycER cells significantly enhanced fibroblast activation and mobilization. As this was accompanied by decreased insulin‐like growth factor binding protein‐6 (IGFBP‐6) and increased insulin‐like growth factor‐1 and IGF‐II (IGF‐I, IGF‐II) in the CM, IGFs were investigated as key chemotactic factors. Silencing IGFBP‐6 or IGF‐I or IGF‐II expression in epithelial cells or blocking Insulin‐like growth factor 1 receptor (IGF‐1R) activity on fibroblasts significantly altered fibroblast mobilization. Exposure of WI‐38 fibroblasts to CM from induced MCF10A‐MycER cells or to IGF‐II upregulated FAK phosphorylation on Tyr 397, as well as the expression of α‐smooth muscle actin (α‐SMA), features associated with CAF phenotype and increased cell migratory/invasive behavior. In three‐dimensional (3D)‐organotypic assays, WI‐38 or human primary fibroblasts, preactivated with either CM from MCF10A‐MycER cells or IGFs, resulted in a permissive TME that enabled nontransformed MCF10A matrix invasion. This effect was abolished by inhibiting IGF‐1R activity. Thus, breast epithelial cell oncogenic activation and stromal fibroblast transition to CAFs are linked through the IGFs/IGF‐1R axis, which directly promotes TME remodeling and increases tumor invasion. Abstract : What's new? The paracrine mechanisms by which tumor‐derived factors promote the transition of normal fibroblasts to cancer‐associated fibroblasts (CAFs) remain largely undefined. Here, in co‐cultures of patient‐derived primary fibroblasts and c‐Myc‐expressing human mammary epithelial cells, c‐Myc upregulation was found to induce fibroblast recruitment and activation via increased IGF/IGF‐1R activity. Moreover, exposure to conditioned medium from c‐Myc‐expressing mammary epithelial cells resulted in fibroblast acquisition of a CAF‐like phenotype and increased matrix invasion by otherwise non‐invasive mammary epithelial cells. The findings shed light on paracrine fibroblast activation during early epithelial tumor development and identify novel therapeutic targets to counteract the tumor‐supportive role of stromal fibroblasts.